Chemical Peel and Its Implications - Alam, Dr Munir (International Journal of Innovative Research in Medical Science, 2020)
Background/Objectives: The chemical peels may be used to help ameliorate the scars, to destroy premalignant and /or malignant lesions, unsightly pigmentation etc. The treatment modalities used to produce a controlled injury are dermabrasion, chemical peels and photoepilation (LASER and IPL). Only if the injury is in the proper tissue plane can the desired result be achieved. If too superficial, the results will be disappointing. If too deep, the results can be catastrophic. Material and Methods: The author has introduced newer formula into the world of chemical peeling according to the depth of peeling agent penetration. Superficial Medium Deep TCA 15 gm TCA 10 gm TCA 35 gm Croton oil Mandelic acid 5 gm Septisol Sesame oil Salicylic acid 15 gm Glyserine Distill water Sesame oil Croton oil Croton oil Distill water Distill water PAKPEEL This is a prospective study of 3 years from Aug 2016 to Aug 2019. In this study, total number of 216 consecutive chemical peels on 54 patients over a 3-year period were performed. Age distribution ranges from 20 years to 55 years. Results: The results achieved with these newer chemical formula are highly satisfactory (80-90%) for almost all skin conditions treated. Conclusion: In our office setting practice, we perform approximately four sessions of chemical peel weekly and continue skin lightening/spot protection creams and sun protection. This study corroborate evidence superiority of our selected chemical formula.